Conoid tubercle angle: attention should be paid to supraclavicular plate fixation - Bin Zhao; Wenqian Zhao; Isaac Assan; Rongxiu Bi (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background The surgical protocol of ORIF for the treatment of mid-shaft clavicle fractures is common. However, poor plate fit or overhang usually occurs when the straight plate is selected for superior fixation. This is because the upper edge of the clavicle is not flat but has an angulation near the conoid tubercle. We termed that angulation, conoid tubercle angle (CTA). Supposed the straight plate is forcibly attached to the surface of the clavicle, it will potentially cause misalignment of the fracture end and with that comes a change of CTA. In this case, choosing the contoured plate, such as a commercial pre-contoured anatomic plate or manual-contoured plate, for superior fixation seems to meet the requirements for both plate fit and fracture alignment. Hence, we retrospectively compared the radiological parameters, including the plate overhang, and the alignment of the fractures reflected by the CTA, between the contoured plate (CP) and straight plate (SP) groups, to draw attention to the CTA and its effects to supraclavicular plate fixation. Methods From March 2018 to April 2021, 217 patients with clavicle fractures that met the inclusion criteria but not the exclusion criteria were included in our study. 112 patients were enrolled into the straight plate group (SP) and 105 patients into the contoured plate group (CP). Besides that, 154 healthy adults were recruited into the health group (HA). Results Patients were followed up for 6 to 40 months postoperative. A normal CTA (164.54 ± 4.78°) was obtained from the HA group. There were 50 cases with plate overhang in the SP group, which presented a statistical difference in comparison with the CP group. The value of CTA (169.65 ± 5.84°) in the SP group also indicated a statistical difference in comparison with the normal CTA. Subgroup analysis showed that the CTA (165.88 ± 5.42°) in the overhang subgroup (O) had no statistical difference in comparison with the normal CTA, but the CTA (172.68 ± 4.18°) in the non-overhang subgroup (N-O) had. 3 cases experienced non-traumatic re-fracture (within 3 months after the removal of the fixation) in the O subgroup; 10 cases experienced a poor reduction in the N-O subgroup. In the CP group, the CTA was 166.79 ± 5.68°, which indicated a statistical difference with the SP group. Subgroup analysis was performed, including the manual-contoured plate subgroup (M-C) and commercial pre-contoured anatomic plate subgroup (P-C). The value of CTA (M-C, 166.97 ± 6.33°; P-C, 166.44 ± 6.33°) manifested a statistical difference in comparison with the N-O subgroup. 2 and 8 cases, respectively, had screw loosening and poor reduction in the M-C subgroup. No postoperative complication occurred in the P-C subgroup. Conclusion CTA is a useful reference in the evaluation of the reduction obtained on radiographic examination, and a reference guiding the plate contouring. The commercial pre-contoured anatomic plate provides a normal CTA and well fits the biomechanical characteristics of the clavicle, which can be recommended for superior fixation.